2015
DOI: 10.4238/2015.october.29.19
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ras-related protein 25 predicts chemotherapy resistance and prognosis in advanced non-small cell lung cancer

Y F1,
et al.

Abstract: ABSTRACT. Ras-related protein 25 (Rab25) is involved in many human malignancies. However, its role in chemotherapy response and prognosis in advanced non-small cell lung cancer (NSCLC) remains unknown. Therefore, we investigated the relationship between Rab25 and chemotherapy sensitivity and prognosis in NSCLC. Rab25 expression was assessed using immunohistochemistry in 324 advanced NSCLC patients. Its correlations with clinical features were analyzed. Sensitivity to cisplatin (DDP) was compared between DDP-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Univariate and multivariate cox regression analyses indicated that Rab25 might be an independent prognostic factor of HCC. Similar to our nding, a large number of researches had demonstrated that Rab25 had potency to predict the overall survival and disease-free survival of tumors [24,25]. Moreover, metastasis and TNM stage both were independent factors in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Univariate and multivariate cox regression analyses indicated that Rab25 might be an independent prognostic factor of HCC. Similar to our nding, a large number of researches had demonstrated that Rab25 had potency to predict the overall survival and disease-free survival of tumors [24,25]. Moreover, metastasis and TNM stage both were independent factors in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The same Rab can be up-regulated or down-regulated in different cancers, like the aforementioned Rab31. Rab25 is another well-characterized Rab in this respect and plays a key role in the aggressiveness, prognosis and metastasis of multiple cancer phenotypes including renal cell carcinoma [115], gastric cancer [116], ovarian cancer [117], and lung cancer [118]. Rab25 belongs to the Rab11 subfamily and is also called Rab11c based on sequence homology and is shown to recycle endocytosed membrane proteins [119].…”
Section: Cancermentioning
confidence: 99%
“…After that, accumulating studies have revealed the aberrant expression of Rab25 and its associations with development, progression and prognosis of numerous types of human cancers. For example, Cao et al [9] showed the overexpression of Rab25 protein in gastric cancer compared to adjacent normal gastric tissues by immunohistochemistry and Western blot, and also confirmed that it promoted the invasion and metastasis of gastric cancer; Mitra et al [15] substantiated a striking context dependent role of Rab25 in breast cancer where Rab25 may be amplified and enhanced aggressiveness in luminal B cancers while in claudin-low tumors, Rab25 may be lost implying possible anti-tumor functions; Zhang et al [12] indicated that Rab25 may promote metastasis of bladder cancer via inducing the epithelial-mesenchymal-transition process and activating Akt/GSK-3β/Snail signaling pathway; Li et al [13] revealed that high levels of Rab25 expression were correlated with renal cell carcinoma invasion classification, lymph-node metastasis and pathological stage; Liu et al [20] also identified Rab25 as a potential prognostic biomarker in clear cell renal cell carcinoma; Geng et al [25] found that Rab25 was overexpressed in human hepatocellular carcinoma and may contribute to cancer cell proliferation and invasion possibly through regulation of the Wnt signaling pathway; Ma et al [26] indicated that Rab25 expression was a potential prognostic index for advanced non-small cell lung cancer patients and its inhibition might improve chemosensitization in non-small cell lung cancer treatment. In contrast, the data of Te′llez-Gabriel et al [14] supported a tumor suppressor role for Rab25 in head and neck squamous cell carcinoma and its potential use to identify locally advanced patients with a high probability of survival after genotoxic treatment; Goldenring et al [16] reported that colorectal adenocarcinomas with low Rab25 correlated with shorter patient survival.…”
Section: Discussionmentioning
confidence: 99%